El Salvador : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for El Salvador. (IMF Staff Country Reports; Country Report, 2022)
The pandemic interrupted ten years of growth, but El Salvador is rebounding quickly. Robust external demand, resilient remittances, and a sound management of the pandemic-with the help of a disbursement under the Rapid Financing Instrument (RFI) (SDR287.2 million or USD 389 million) approved in April 2020-are supporting a strong recovery. Persistent fiscal deficits and high debt service are leading to large and increasing gross fiscal financing needs.